Everyday security threats : perceptions, experiences, and consequences - Stevens, Daniel; Vaughan-Williams, Nick (Manchester Security, Conflict & Peace, 2016)
Everyday security threats explores public perceptions of security threats in contemporary Britain, using data from extensive fieldwork and drawing on perspectives from International Relations, security studies and political psychology.